THE INFLUENCE OF THE CASHLESS PAYMENT SYSTEM AND TERMINAL FACILITIES ON SERVICE USER SATISFACTION AT THE PELINDO TANJUNG BALAI KARIMUN PASSENGER TERMINAL - Yusrizal; Pangihutan Tua Manurung, Anto Sakti; Sulistian, Fahmi; Cardiana; Irwanda (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
Karimun is a boarding and alighting service for domestic and international passengers. To support passenger services, PT Pelabuhan Indonesia (Persero) continues to strive to improve its passenger terminal, both in terms of facilities and services. The Karimun Regent Regional Government remains committed to improving the regional economy, especially related to the tourism sector and maritime industry. Tanjung Balai Karimun Passenger Terminal offers excellent opportunities and prospects as it is strategically important for the positive impact of IMS-GT (Indonesia, Malaysia and Singapore-Growth Triangle). In the digital age like now, money is an important part of the human economy. Money can be used for transactions that are acceptable to humans. Service quality has a very good and significant influence on passenger terminal facilities. Ha is accepted and the results of the t test calculation which is the hypothesis that service quality has a very important influence on passenger terminal facilities produces a value of t = 2.445 at a significance level of 0.008. And T count (2.445) > T table (2.01), the significance value is 0.008, which is 0.05 smaller. The value of port services is also reflected in the embarkation and disembarkation options for sea passengers at the Tanjung Balay Karimun Indonesia Domestic Port Terminal.